Evaluating the Knowledge, Attitude and Practices of Nursing Mothers towards Exclusive Breastfeeding in Tano North District - Sampson, Gilbert Owiah; Mohammed, Barikisu; Iddrisu, Ibrahim Nshinmi (International Journal of Medical and Health Sciences Research, 2020)
The objective of the study was to evaluate the knowledge, attitude and practices of exclusive breastfeeding among nursing mothers in the Tano North District. Cross sectional study type was used to conduct the study. A semi structured questionnaire was used in the study to collect data from the respondents. Random sampling technique was used to select 100 nursing mothers who were breastfeeding in the Tano North District. The study revealed that maternal knowledge, practices, age, marital status and level of education can influence exclusive breastfeeding. It was again revealed that 86% of the respondents were mature mothers. It was recommended that mothers should introduce exclusively breastfeeding to their babies at least for the first six months of life to achieve optimal growth, development and health.